PENGAWASAN PEREDARAN ROKOK ILEGAL OLEH KANTOR PENGAWASAN DAN PELAYANAN BEA DUMAI - Farando, Al; Gultom, Elfrida Ratnawati (Ensiklopedia of Journal, 2024)
This study aims to determine the supervision of the circulation of illegal cigarettes by the Customs and Excise Supervisory and Service Officer of Type C Madya Pabean in Tembilahan City, Dumai. The assessment indicators used include determining work standards, measuring work results, taking action/sanctions, correcting, and rectifying. This type of research uses descriptive qualitative, namely analyzing or directly describing social life by describing social life. The data collection techniques used in this study were observation, interviews, and documentation techniques. Then the data analysis technique that the writer uses in this research is Interactive Huberman. Based on this analysis technique, the researcher assesses and concludes that the Supervision of Illegal Cigarette Circulation by the Supervisory Officer and Customs and Excise Service Type Madya Customs Dumai has not run optimally enough, because there are problems, namely the lack of optimal socialization to the public, which causes the circulation of illegal cigarettes to continue, and the lack of human resources at the Customs Office to supervise the circulation of illegal cigarettes.Keywords: Controlling, Circulation, Illegal Cigarettes